CIRI-CIRI TOKOH DALAM NOVEL 9 MATAHARI KARYA ADENITA DAN KELAYAKANNYA SEBAGAI BAHAN AJAR SASTRA INDONESIA DI SMA - Ibrahim Toha; muhammad fuad; kahfie nazaruddin (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
The problem of this research was how is the characteristic of characters in 9 Matahari novel by Adenita and its feasibility as the lesson of Indonesia literature in Senior High School (SMA). The objectives of this research were to describe the characteristic of characters and its classification in 9 Matahari novel by Adenita and also to determine its feasibility as the lesson of Indonesia literature in senior high school (SMA).The research method that was used in this research was qualitative method. The data source of this research was 9 Matahari by Adenita. Data collecting technique and data analysis in this research was text analysis technique.The result of the research showed that some characteristic of the characters which were included  in this novel, that were clever, generous, principled, spit-fire, authoritative, active, interest, assertive, like to give an advice, pessimist, lover, optimist, willing sacrifice, grateful, smart, tough, strong will, high aspiration, and loyal to the religion. Based on its character classification, (a) the main character was Matari Anas, he was generous, interest, lover, grateful, loyal to the religion, principled, assertive, tough, strong will, high aspiration, optimist, clever, active, and smart. Additional characters were Yati Ayati, she was generous, interest, and liked to give an advice; aunt Erna, she was generous; Hera, she was interest, willing sacrifice, authoritative, and clever; Pandu, He was  interest, and spit-fire; Lena, she liked to give an advice; Mom Hesti, she liked to give an advice; Arga, He liked to give an advice; Dedi, he liked to give an advice, (b) protagonist character was Matari Anas and antagonist character was Biran Anas, (c) static character was Yati Ayati and dynamic character was Biran Anas.9 Matahari novel bu Adenita was suitable to be used an alternative lesson of Indonesia literature in Senior High School (SMA). It was based on the election criteria of  literature learning, it was seen from three aspects, they were curriculum aspect, literature aspect, and character education aspect.being observed from character education aspect, the characteristic of the characters which were described by the author in this novel can be used as a lesson. moreover, the characteristic of characters that can be used as lesson of character education are smart, generous, principled, active, interest, assertive, like to give an advice, lover, optimistic, willing sacrifice, grateful, clever, tough, strong will, high aspiration, and loyal to the religion.Key words: characteristic of characters, classification of characters, advisability